Pengaruh Media Pembelajaran Geometri Bangun Ruang Berbasis Google Sites Terhadap Hasil Belajar Kelas V - Hidayati, Widya Ayu Kurnia; Wulandari, Rika (Yayasan Arrahman Nahdlatul Wathan, 2024)
The purpose of this research is to determine whether there is an influence of Google Sites-based spacial geometry learning media on the learning outcomes of class V students. This type of research is quasi-experimental with a Nonequivalent Control Group Design. The population in this study were all fifth grade students at SDN Bugih 1 Pamekasan. The sampling technique used Simple Random Sampling, with a sample of 44 students. Research data was collected using learning outcomes tests, observations of learning implementation, and student response questionnaires. The research results showed that the average learning outcome for the control class after being treated was 0.00 and the average learning outcome for the experimental class after being treated was 83.33. Then the results of the independent sample t-test hypothesis test from student learning outcomes after being given treatment obtained a significance value of 0.000 and tcount > ttable, namely 4.234 > 2.021. Based on decision making in the independent sample t-test, if the significance value is <0.05 and tcount > ttable, then Ho is rejected and Ha is accepted, that is, there is a significant difference between the learning outcomes of the control class and the experimental class, and the learning outcomes of the class. The experiment was better than the control class learning results. So it can be concluded that there is a significant difference in average learning outcomes between the control class and the experimental class, there is an influence of Google Sites-based spatial geometry learning media on the learning outcomes of class V students at SDN Bugih 1 Pamekasan